Photosynthesis in reproductive structures: costs and benefits - Raven, John A. (J Exp Bot, 2015)
The role of photosynthesis by reproductive structures during grain-filling has important implications for cereal breeding, but the methods for assessing the contribution by reproductive structures to grain-filling are invasive and prone to compensatory changes elsewhere in the plant. A technique analysing the natural abundance of stable carbon isotopes in soluble carbohydrates has significant promise. However, it depends crucially on there being no more than two sources of organic carbon (leaf and ear/awn), with significantly different (13)C:(12)C ratios and no secondary fractionation during grain-filling. The role of additional peduncle carbohydrate reserves represents a potential means for N remobilization, as well as for hydraulic continuity during grain-filling. The natural abundance of the stable isotopes of carbon and oxygen are also useful for exploring the influence of reproduction on whole plant carbon and water relations and have been used to examine the resource costs of reproduction in females and males of dioecious plants. Photosynthesis in reproductive structures is widespread among oxygenic photosynthetic organisms, including many clades of algae and embryophytes of different levels of complexity. The possible evolutionary benefits of photosynthesis in reproductive structures include decreasing the carbon cost of reproduction and ‘use’ of transpiratory loss of water to deliver phloem-immobile calcium Ca(2+) and silicon [Si(OH)(4)] via the xylem. The possible costs of photosynthesis in reproductive structures are increasing damage to DNA from photosynthetically active, and hence UV-B, radiation and the production of reactive oxygen species.